Literatura mądrościowa a Boecjuszowe "O pocieszeniu jakie daje filozofia" - Kijewska, Agnieszka (Verbum Vitae, 2021)
In this article, I have sought to draw numerous parallels between Boethius’s thoughts and the content of the Book of Wisdom. The starting point of these considerations is that in Boethius’ On the consolation of philosophy there is a direct quote from the Book of Wisdom (8:1). The similarities and analogies mined in the course of the analysis concern primarily ethical issues: the question of man’s relationship to God, human suffering, and the question of evil. In the context of the most pressing issues that appear in the study of Boethius’s thinking, such as the question of his Christianism or sources of Neoplatonic influences, perhaps, based on these analogies, it will be possible to move a little closer toward solving these problems.